QUALITY CONTROL OF PACKED RED CELL (PRC) PRODUCT IN BLOOD DONATION UNIT - Silvi Astutiningtiyas; Luthfi Rusyadi; Yeti Kartikasari (Poltekkes Kemenkes Semarang, 2022)
Blood Transfusion Service Standards aim to ensure the safety high quality and sufficient blood services sufficient blood reserve. The standard for blood requirements for each country according to WHO is at least 2% of the total population. The population in Indonesia has increased every year so the need for blood is also increasing causing demands for causing the quality of blood services to be better. One of the demands for the quality of blood services by knowing is to know the quality control of the blood produced. One of the blood products produced is PRC. PRC Packed Red Cells quality control checks must be carried out to determine the quality of the PRCs produced. This study aims to determine the overall quality control of PRC and the results of PRC quality control based on (volume, hemoglobin, hematocrit, hemolysis, and bacterial contamination) in the Blood Donation Unit of Banyumas Regency in 2020. This type of research is descriptive. Sampling technique with a sample quota as much as the total sample quality control packed red cell test obtained 1% of the total production of PRC components every month in the Blood Donation Unit of Banyumas. The QC research results were obtained from 430 PRC samples that met the passing standards: 426 samples (99%) volume, 426 samples (99%) hemoglobin, 380 samples (88%) hematocrit, 429 samples (99.7%) hemolysis, and 426 samples (99%) passed from bacterial contamination. The number of QCs who qualified was 373 samples (87%). These results indicate that the 2020 PRC QC obtained good and satisfying results.